Tindak Pidana Pembunuhan Berencana Disertai Kekerasan Seksual: Studi Kasus di Tarutung - Hutapea, Rinsan Maratur; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The murder case of Kristina Lasmatiar boru Gultom, a student at Karya Tarutung Private Vocational School, in Pangguan Hamlet, Hutapea Banuarea Village, North Tapanuli Regency, is a form of serious crime involving elements of premeditated murder and sexual violence. This incident occurred on August 4, 2019 and was carried out by the suspect Rinto Hutapea, who was the victim's neighbor. This crime began with harassment, then continued with beatings, strangulation to death, and allegations of rape which were strengthened by the results of an autopsy and DNA examination. This study aims to identify the criminal elements fulfilled in the case and analyze its handling from the perspective of positive criminal law and community responses through customary law mechanisms.